Tanggung Jawab Hukum atas Perbuatan Malpraktik yang Dilakukan oleh Notaris Protokol - Susilo Meddy Tunggeleng (Fakultas Syariah IAIN Laa Roiba Bogor, 2024)
The malpractice actions carried out by a notary in a broad sense constitute forms of denial, deviation, or arguably a lack of ability to perform their duties and responsibilities, either intentionally or negligently, which can be held accountable to the notary for fulfilling their professional obligations based on the trust given to them. This article discusses whether malpractice actions committed by a notary can be categorized as criminal acts and the legal consequences of malpractice committed by a protocol notary. This research is a normative study, also known as doctrinal research. Notarial malpractice actions can be categorized as criminal acts, namely errors and negligence, and this negligence can be divided into culpa lata and culpa levis. In cases of malpractice, it mostly falls under culpa lata, thus criminal sanctions can be imposed. In the event that a notary designated as a protocol holder refuses to hand over the protocol for reasons that are unacceptable to the minister, the respective notary may be sanctioned by the Ministry of Law and Human Rights, Professional Organizations, or the Minister in accordance with the provisions of laws and regulations. Sanctions for violations of duties, prohibitions, professional ethics, and notarial codes of conduct may result in temporary suspension or dishonorable discharge from office. Violations of the provisions as referred to in the Notary Law and Notarial Code of Ethics.